1978
DOI: 10.1037/0022-0167.25.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Initial client expectancies in time-limited counseling.

Abstract: This experiment assessed the effects on initial expectancies of whether counseling was time-limited (12 sessions), of the interaction of time limits with the chronicity of the client's problem, and of the rationale given for time limits (time limits effective/appropriate vs. a long waiting list). Eighty female college students were asked to place themselves into the role of a client they saw interacting with a counselor on film. Pre-and postfilm written material manipulated the independent variables. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…All studies conducted before 1975 found some type of negative effects of waiting for services (Levy, 1963; Sinnett & Danskin, 1967). From 1975 to 1982, four studies had mixed or inconclusive results (Christensen et al 1975; McKitrick & Gelso, 1978; Schiller, 1976; Shueman et al, 1980), and one study found minimal negative effects (Archer, 1981). Since 1982, four studies have failed to find significant negative effects (Anderson et al, 1987; Archer, 1984b; Freund et al, 1989; May, 1990), one study had mixed results (Rodolfa et al, 1983), and one study had incidental reports of negative effects (Kokotovic & Tracey, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies conducted before 1975 found some type of negative effects of waiting for services (Levy, 1963; Sinnett & Danskin, 1967). From 1975 to 1982, four studies had mixed or inconclusive results (Christensen et al 1975; McKitrick & Gelso, 1978; Schiller, 1976; Shueman et al, 1980), and one study found minimal negative effects (Archer, 1981). Since 1982, four studies have failed to find significant negative effects (Anderson et al, 1987; Archer, 1984b; Freund et al, 1989; May, 1990), one study had mixed results (Rodolfa et al, 1983), and one study had incidental reports of negative effects (Kokotovic & Tracey, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…For wait-list clients who continue with counseling, Freund et al (1989) found no relationship between the length of wait and hopefulness that counseling would alleviate presenting problems or client perceptions of the counselor's trustworthiness, expertness, or attractiveness. In an analogue study, McKitrick & Gelso (1978) studied clients' reactions to time limits on therapy that were based on either a rationale that a wait list required such limits or that time-limited therapy was considered to be more effective. These authors found no difference in their initial survey of client reactions, but did note more negative comments about the wait-list rationale on a postexperiment questionnaire.…”
Section: Effects Of Waiting For Servicementioning
confidence: 99%
“…Christen, Birk, and Sedlacek (1975) also concluded from a telephone survey that clients who had been on a waiting list and did not show up for their first counseling session were probably dissatisfied with their experience. In an analogue study examining time-limited counseling and initial client expectancies, McKitrick and Gelso (1978) found that 8 out of 20 subjects expressed negative opinions toward a waiting list rationale.…”
mentioning
confidence: 99%
“…Preparation of clients for time-limited treatment is also vital (Budman & Gurman, 1983). As McKitrick and Gelso (1983) found, a clear presentation of the rationale for time-limited treatment will result in clients' positive initial reactions and outcome expectancies.…”
Section: Evaluation/planning Factorsmentioning
confidence: 99%